Emotional intelligence and dance: a systematic review - San-Juan-Ferrer, Barbara; Hípola, Pedro (Research in Dance Education, 2020)
In this review, the background to the construct of Emotional Intelligence and its more widely accepted perspectives are presented. The scientific literature on the relationship between dance and Emotional Intelligence was obtained from the Web of Science (58) and Scopus (5) databases, and the results of these investigations were analysed. Dance is understood from a pragmatic point of view, without distinguishing the dance discipline of each of the analysed studies; likewise, we encompass any level of practice within this art and the different stages of life among practitioners. In summary, dance is understood as a beneficial component for the emotional and affective development of the human being, and it is presented as an element that favours different aspects of the Emotional Intelligence and others related to it.
Keywords: emotional intelligence; dance; emotion; artistic-expressive movement; non-verbal communication; WOS; Scopus